Immigrating into a Recession: Evidence from Family Migrants to the United States - Barsbai, Toman; Steinmayr, Andreas; Winter, Christoph (Journal of Labor Economics, 2025)
We analyze how economic conditions at the time of arrival affect the economic integration of family-sponsored migrants in the U.S. Our identification strategy exploits long waiting times for family-sponsored immigration visas that decouple the migration decision from economic conditions at the time of arrival. A one pp higher unemployment rate at arrival decreases annual wage income by four percent in the short run and two percent in the longer run. The loss in wage income is the result of substantial occupational downgrading, lower hourly wages, and a reduction in working hours. Family migrants who immigrate into a recession draw on migrant and family networks to mitigate the negative labor market effects. As a result, they take up occupations with higher concentrations of fellow countrypeople. They are also more likely to reside with family members, potentially reducing their geographical mobility.